Second‐generation corneal deformation signal waveform analysis in normal, forme fruste keratoconic, and manifest keratoconic corneas after statistical correction for potentially confounding factors. Issue 10 (October 2015) - Zhang, Lijun; Danesh, Jennifer; Tannan, Anjali; Phan, Vivian; Yu, Fei; Hamilton, Rex D.
Abstract : Purpose : To evaluate the difference in corneal biomechanical waveform parameters between manifest keratoconus, forme fruste keratoconus, and healthy eyes with a second‐generation biomechanical waveform analyzer (Ocular Response Analyzer 2). Setting : Jules Stein Eye Institute, University of California, Los Angeles, California, USA. Design : Retrospective chart review. Methods : The biomechanical waveform analyzer was used to obtain corneal hysteresis (CH), corneal resistance factor (CRF), and 37 biomechanical waveform parameters in manifest keratoconus eyes, forme fruste keratoconus eyes, and healthy eyes. Useful distinguishing parameters were found using t tests and a multivariable logistic regression model with stepwise variable selection. Potential confounders were controlled for. Results : The study included 68 manifest keratoconus eyes, 64 forme fruste keratoconus eyes, and 249 healthy eyes. There was a statistical difference in the mean CRF between the normal group (10.2 mm Hg ± 1.7 [SD]) and keratoconus group (6.3 ± 1.9 mm Hg) ( P = .003), and between the normal group and the forme fruste keratoconus group (7.8 ± 1.4 mm Hg) ( P < .0001). There was no statistical difference in the mean CH between the normal group and the keratoconus group or the forme fruste keratoconus group. The CRF, height of peak 1 (P1) ( P = .001), downslope of P1 (dslope1) ( P = .027), upslope of peak 2 (P2) ( P = .004), and downslope of P2 ( P = .006) distinguished the normal group from the keratoconus groups. The CRF, downslope of P2 derived from upper 50% of applanation peak ( P = .035), dslope1 ( P = .014), and upslope of P1 ( P = .008) distinguished the normal group from the forme fruste keratoconus group. Conclusion : Differences in multiple biomechanical waveform parameters can differentiate between healthy and diseased conditions and might improve early diagnosis of keratoconus and forme fruste keratoconus. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.